Remaja Bermasalah Hukum di Panti Sosial Hiti-Hiti Hala-Hala: Kajian Pastoral - Aranscha R Kulaleen; Cl Pattinama (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
These teenagers need encouragement and motivation and strengthening in dealing with every case they have. For them, the problems they face have considerably narrowed the space for movement. They can no longer have more time together with their families. They are not free to express themselves at school. They are no longer able to play and hang out like teenagers in general. The problem faced by these teenagers is the findings of research conducted at the Social Home of Hiti-hiti Hala-hala. With pastoral studies, researchers found that there is real support in the form of pastoral care. Adolescents can face life's problems, find the meaning behind these problems, and have the courage to make decisions to live a better life in the future.